2019
DOI: 10.3389/fimmu.2019.01257
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Derivative BA5, Attenuates Inflammation and Fibrosis in Experimental Chronic Chagas Disease Cardiomyopathy by Inducing IL-10 and M2 Polarization

Abstract: Chronic Chagas disease cardiomyopathy (CCC) is a major cause of heart disease in Latin America and treatment for this condition is unsatisfactory. Here we investigated the effects of BA5, an amide semi-synthetic derivative betulinic acid, in a model of CCC. Mice chronically infected with T. cruzi were treated orally with BA5 (10 or 1 mg/Kg), three times per week, for 2 months. BA5 treatment decreased inflammation and fibrosis in heart sections but did not improve exercise capacity or ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Considering the role of IL-10 in CCC, a recent work shows that a betulinic acid derivative is able to reduce inflammation and fibrosis, associated with a significant increase in serum IL-10 levels, in an experimental model of chronic Chagas disease. However, these authors do not report any changes in the electrocardiographic or ergometry registers resulting from treatment (35). Interestingly, it has been shown that IL-10 inhibits the production of pro-inflammatory cytokines signaled by the NF-kB and ERK/MAPK pathways through upregulation of SOCS3 in cardiomyocytes infected in vitro with T. cruzi (36).…”
Section: Introductionmentioning
confidence: 86%
“…Considering the role of IL-10 in CCC, a recent work shows that a betulinic acid derivative is able to reduce inflammation and fibrosis, associated with a significant increase in serum IL-10 levels, in an experimental model of chronic Chagas disease. However, these authors do not report any changes in the electrocardiographic or ergometry registers resulting from treatment (35). Interestingly, it has been shown that IL-10 inhibits the production of pro-inflammatory cytokines signaled by the NF-kB and ERK/MAPK pathways through upregulation of SOCS3 in cardiomyocytes infected in vitro with T. cruzi (36).…”
Section: Introductionmentioning
confidence: 86%
“…Polarization of M1 macrophages results in the chronic in ammation of white adipose tissue and is reported to be highly correlated with obesity and metabolic disorders [37] . On the other hand, cytokines, such as interleukin 4 (IL-4), interleukin 10 (IL-10), interleukin 13 (IL-13)and transforming growth factor-β (TGF-β), tend to polarize macrophages toward M2 type, which behave as the extinguisher of in ammation and participate in the reconstruction of tissues and reestablishment of vessels [38,39] .Therefore, we further validated the possible in ltration of macrophages in the inguinal WAT. Massive Mac2 + macrophages were present in the WAT slices at week 4 after catgut embedding, and the expression of molecular markers and polarization related cytokines of M2 macrophages increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were related to a reduction of pro-inflammatory molecules, such as IFN-γ, IL-1β, and TNF, and increased IL-10 production. Moreover, polarization to anti-inflammatory/M2 macrophage phenotype was evidenced by a decrease in the expression of NOS2 and proinflammatory cytokines and the increase in M2 markers, such as Arg1 and CHI3, in mice treated with BA5 ( Meira et al., 2019 ).…”
Section: Immunomodulatory Agents and CCCmentioning
confidence: 99%